Gold in Pyrite within Altai - Sayan Folded Belt Gold Deposits; IOP Conference Series: Earth and Environmental Science; Vol. 21: XVIII International Scientific Symposium in Honour of Academician M. A. Usov: Problems of Geology and Subsurface Development 7–11 April 2014, Tomsk, Russia - Pshenichkin A. Ya. Anatoliy Yakovlevich; Oskina Yu. A. Yuliya Aleksandrovna; Savinova O. V. Olesya Vyacheslavovna; Dolgaya T. F. Tatiana Fedorovna (Mineralogy, Geochemistry and Petrography, 2014)
Title screen